Ciacia Language Maintenance through "House of Culture" Model - Kamaluddin, Kamaluddin; Nurnia, Nurnia (IJLECR (International Journal of Language Education and Cultural Review), 2016)
Local language maintenance has been remarkably attended recently following massive extinction of languages for having been rarely used and not transmitted well to younger generation. This paper reports the findings of a study related to a model which is evidently useful to preserve local language use among students with less comprehension to their local language. The developed model employs local short stories as tools for language perseverance by means of project making which requires students’ active participation mingling with the language. The study indicates that local culture and tradition like short stories is apparently favorable to support and promote the use of local language among students. Thus, it is highly recommended that local culture and tradition be cultivated and developed to preserve language maintenance and involve language users directly and consciously towards language survival.